Gender gap in perspectives of the impacts of degradation and restoration on ecosystem services in Ethiopia - Mponela, Powell; Aynekulu, Ermias; Ebrahim, Mohammed; Abate, Tsion; Abera, Wuletawu; Zaremba, Haley; Elias, Marlène; Tamene, Lulseged D. (Wiley, 2023)
The importance of land restoration has garnered increasing attention on the global stage through large-scale initiatives such as the Bonn Challenge. However, policies and strategies are often gender-blind and designed in compliance with entrenched social hierarchies, exacerbating pre-existing social inequalities that affect restoration initiatives. The challenge of developing gender-responsive policies and initiatives is accentuated by a persistent lack of sex-disaggregated data concerning men's and women's differing perceptions and experiences. This study aims to help fill this gap by capturing the differences in men and women's perceptions of ecosystem services before and after restoration interventions in Ethiopia. Towards that end, in October 2021, we collected data from fifty-nine (59) paired husband-wife households and six gender-segregated focus group discussions in two regions of Ethiopia: Amhara and Southern Nations, and Nationalities and Peoples (SNNP). Kendall's concordance analysis established a strong degree of disagreement between men's and women's ratings of restoration outcomes for most indicators. Men attributed degradation to landscape conditions and natural forces, while women considered the lack of appropriate restoration strategies as a precursor for accelerated degradation. The study also reveals that men tended to benefit more than women from enhanced ecosystem services post-restoration, with increased labour and land management burdens often falling on the shoulders of women. Based on these findings, we argue that including men's and women's perspectives from the earliest planning phases of restoration initiatives is essential to ensure greater equity in benefit-sharing, mitigate trade-offs for women, and build more nuanced, just and successful approaches to restoration.